The Role of Narratives in Consumer Information Processing - Adaval, Rashmi; Wyer, Robert S. (Journal of Consumer Psychology, 1998)
Participants estimated the attractiveness of vacations described in 2 travel brochures. The information about 1 vacation was conveyed in a narrative that described the sequence of events that would occur. In contrast, information about the other vacation was conveyed in an ostensibly unorganized list. Vacations were generally evaluated more favorably when they were described in a narrative than when their features were simply listed. Moreover, this difference increased when (a) negative features of the vacations were mentioned, (b) pictures accompanied the text information, or (c) recipients were encouraged to imagine themselves having the experiences described. Although narrative forms of information elicited more extreme affective reactions than list forms, this did not account for the difference in their effectiveness. Rather, the advantage of narratives was attributed to (a) their structural similarity to information acquired through daily life experiences and (b) the use of a holistic—as opposed to a piecemeal—strategy for computing judgments.